: Auditoria de gestión a la empresa Telcomexpert S.A de la ciudad de Riobamba provincia de Chimborazo período 2022. - Hernández Vaca, Sheyla Tatiana (2024)
ABSTRACT: The performance audit process not only provides an objective assessment of the company's internal processes, but also an invaluable opportunity to identify areas for improvement and take proactive measures to foster the long-term growth and success of the organization. Considering this context, it is proposed as a subject of study MANAGEMENT AUDIT TO THE COMPANY TELCOMEXPERT S.A., OF THE CITY OF RIOBAMBA, PROVINCE OF CHIMBORAZO PERIOD 2022, with the objective of carrying out a Management Audit in the company TELCOMEXPERT S.A., during the period 2022. This audit was carried out using a mixed methodology, which allowed us to obtain a comprehensive view of the business situation. Quantitative data were used to analyze objective metrics and operational efficiency, as well as qualitative data to evaluate subjective aspects such as management quality and customer perception. Among the main findings were the lack of ethical standards, deficiencies in personnel evaluation, non-compliance with regulations, and problems in supervision and internal communication. In addition, it became evident that compliance with legal regulations has not been fully implemented, which has affected the effectiveness, efficiency and economy of the activities. In conclusion, it is necessary to implement corrective measures and strengthen internal controls to improve efficiency and transparency in the management of the company, thus guaranteeing its integrity and good performance in the long term. This audit offers a valuable opportunity for the continuous improvement of Telcomexpert S.A., ensuring its competitiveness and sustainability in today's market.